UNIT-LINKED INSURANCE PRODUCT MODELLING WITH CONSTANT PROPORTION PORTFOLIO INSURANCE INVESTATION - Jason, Patrick
In recent years, insurance company have been developing Unit-Link Insurance Plan (ULIP) more as it is less risky for the company than traditional product since investment is made in the fund chosen by policyholder and the policyholder himself is the one reaping gains from the investation. Because of its ’high risk, high return’ nature, this type of product have potential for a greater market in Indonesia as it appeals to the younger public which is the population group excess in Indonesia. In ULIP, there are two kinds of risks are concerned about, which are mortality risk and financial market risk. These two behavior will be modeled separately, the financial component using Constant Proportion Portfolio Insurance investation method and the insurance component using Standard Ultimate Survival Model. The purpose of this paper is to present a simple pricing method to determine net single premium of ULIP. A simulation of net single premium calculation will be performed for term life insurance ULIP product of 10 years.